Pemberdayaan disabilitas melalui transfer teknologi budidaya udang bioflok di Kota Banda Aceh (Empowering people with disabilities through the transfer of biofloc shrimp cultivation technology in The City of Banda Aceh) - Putra, Dedi Fazriansyah; Jalil, Zulkarnain; Muhammad, M; Wahab, Gunawan Abdul (Universitas Syiah Kuala, 2023)
Empowerment of people with disabilities through the transfer of biofloc shrimp farming technology in the city of Banda Aceh is a program aimed at enhancing the independence and empowerment of people with disabilities. Biofloc shrimp farming is a technology that utilizes a biofloc system, where bacteria are used to break down waste and provide nutrients for the shrimp. In this system, shrimp can grow faster and healthier compared to conventional shrimp farming methods. The program is in partnership with the Imam Ahmad bin Idris Aceh Foundation located in the village of Alue Naga and will be implemented from August to November 2023. The training will cover the construction of the tank, water management, feeding, shrimp maintenance, and harvesting methods. Additionally, the program will provide initial capital assistance to start biofloc shrimp farming businesses. This program aims to enable people with disabilities to achieve better income and improve their self-reliance. Furthermore, it is expected to increase biofloc shrimp production in the city of Banda Aceh, thereby enhancing the local economy.